Warrior Of The Altaii - Jordan, Robert 1948-2007 (New York : Tor, 2019)
The waterholes of the Plain are drying up, and Wulfgar, leader of the Altaii people faces many other challenges. This is Robert Jordan's never-before-published first novel, which he wrote before his well-known Wheel of Time series.
Keywords: Imaginary places -- Fiction; Queens -- Fiction; Droughts -- Fiction; FICTION -- Fantasy; FICTION -- Fantasy; FICTION -- Fantasy; Droughts; Imaginary places; Queens; Fantasy fiction; Fiction; Fantasy fiction; Fantasy fiction